Laccase/caffeic acid-catalyzed crosslinking coupled with galactomannan alters the conformational structure of ovalbumin and alleviates Th2-mediated allergic asthma - Ishfaq Ahmed; Suidong Ouyang; Shengquan Wu; Haochang Song; Miaoyuan Zhang; Renxing Luo; Peishan Lu; Jiaqi Deng; Tingting Zheng; Yanyan Wang; Xinguang Liu; Gonghua Huang (Food Science and Human Wellness)
Ovalbumin (OVA) is the major allergenic protein that can induce T helper 2 (Th2)-allergic reactions, for which current treatment options are inadequate. In this study, we developed a polymerized hypoallergenic OVA product via laccase/caffeic acid (Lac/CA)-catalyzed crosslinking in conjunction with galactomannan (Man). The formation of high molecular weight crosslinked polymers and the IgG-binding were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting. The study indicated that Lac/CA-catalyzed crosslinking plus Man conjugation substantially altered secondary and tertiary structures of OVA along with the variation in surface hydrophobicity. Gastrointestinal digestion stability assay indicated that crosslinked OVA exhibited less resistance in simulated gastric fl uid (SGF) and simulated intestinal fluid (SIF). Mouse model study indicated that Lac-Man/OVA ameliorated eosinophilic airway inflammatory response and efficiently downregulated the expression of Th2-related cytokines (interleukin (IL)-4, IL-5, and IL-13), and upregulated IFN-γ and IL-10 expression. Stimulation of bone marrow-derived dendritic cells with Lac-Man/OVA suppressed the expression of phenotypic maturation markers (CD80 and CD86) and MHC class Ⅱ molecules, and suppressed the expression levels of proinfl ammatory cytokines. The knowledge obtained in the present study offers an effective way to acquire a hypoallergenic OVA product that can have a therapeutic effect in alleviating OVA-induced allergic asthma.